(untitled) (Global Journal of Human-Social Science, 2015)
This research paper explores different layers of resistance in Aimé Césaire’s A Tempest through the characterization of Caliban and how Aimé Césaire de-mystifies the notions of the representation of colonial politics in a counter discursive way. Caliban, who was not a focused character and was applied in The Tempest as an antithesis to Prospero, in broader sense the so called "rational", "civilized" colonizers, has been given voice by Césaire to retort back to William Shakespeare. In this sense this adaptation for the black theatre is a commentary of the original text. Actually Aimé Césaire comments on the misrepresentation of judging and generalizing the "black" as savage, lustful and irrational. Moreover, this research addresses how the vocal resistance of Caliban is related to the author’s philosophy of negritude. This paper also discusses how the language of the colonizers can be interpolated to the process of selfrepresentation without any spectacle. Caliban’s urge for reestablishing his identity can be seen as the recuperation of the distorted "black" identity caused by the aggression of the colonial power and cultural domination. Caliban’s utmost strive to go back to the root is synonymous with the endeavor of the colonized people to fight back against colonial modes and manipulations through negritude.